Need Analysis of Teaching English for Mechanical Engineering at Vocational Universities in Banjarmasin : a Literature Review - Rahma Pitria Ningsih; Sulaiman Sulaiman (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2023)
This article explores the need analysis of teaching English for mechanical engineering students in vocational universities, focusing on the local context of Banjarmasin. The review draws on existing literature regarding English for Specific Purposes (ESP), vocational education, and mechanical engineering to identify the critical language skills required for students in this field. The research highlights the importance of curriculum alignment with industry demands and outlines key linguistic challenges faced by students. The analysis also emphasizes the necessity for vocational institutions to adapt their English language curricula to meet the specific needs of mechanical engineering students.